Correlación experiencia-teoría en el Reactor RA-3 - Pasquini, E.; Pieroni, Nestor B.; Rapoport, Horacio; Ricabarra, Guillermo H.; Solanilla, Roberto B. A. (Comisión Nacional de Energía Atómica; Argentina, 1967)
Fil: Pasquini, E. Comisión Nacional de Energía Atómica; Argentina